Pemberdayaan Masyarakat Melalui Potensi Lokal untuk Pengembangan Ekonomi Kreatif di Kelurahan Lelamase - Risma Damayanti; M. Rimawan; Alwi Alwi; Imel Putri Cahyati; Indri Sulistiyanti (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to explore and develop the local potential in Lelamase Village to improve the creative economy of the local community. Through a community empowerment approach, this research identifies various potential natural resources and local skills that can be used to create creative products of economic value. Empowerment activities include training, business assistance, and marketing facilitation to encourage the community to produce superior products in accordance with market demand. The results of the study show that through the optimization of local potential and collaboration between communities, there is an increase in income and business skills among the residents of Lelamase. With a sustainable strategy, this empowerment effort is expected to become a model for creative economy development that is able to strengthen economic independence and improve the standard of living of the community in Lelamase Village..